2007
DOI: 10.1007/s10926-007-9078-z
|View full text |Cite
|
Sign up to set email alerts
|

Are Pain Intensity and Pain Related Fear Related to Functional Capacity Evaluation Performances of Patients with Chronic Low Back Pain?

Abstract: Introduction: Pain related fear and pain intensity have been identified as factors negatively influencing Functional Capacity Evaluation (FCE) performances in patients with CLBP. Conflicting results have been reported in the literature. The objective of this study was to analyze the relationships between pain intensity and pain-related fear on the one hand, and performances during an FCE on the other hand in two samples of patients with chronic low back pain (CLBP). Methods: Two cross sectional observation stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 33 publications
1
38
1
3
Order By: Relevance
“…As a complementary explanation, it has been suggested that pain-related beliefs, such as fear avoidance due to longstanding pain, are more important determinants of disability in patients with musculoskeletal disorders than intensity of pain per se (18). Thus the belief that rapid movement exacerbates pain (4,19,36) could potentially limit neural drive. Therefore, changes in pain-related beliefs during the course of training, and not only reduction of pain per se, may have contributed to the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…As a complementary explanation, it has been suggested that pain-related beliefs, such as fear avoidance due to longstanding pain, are more important determinants of disability in patients with musculoskeletal disorders than intensity of pain per se (18). Thus the belief that rapid movement exacerbates pain (4,19,36) could potentially limit neural drive. Therefore, changes in pain-related beliefs during the course of training, and not only reduction of pain per se, may have contributed to the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Pain related fear is defined as the development of sensitivity state towards injury that may cause pain and disproportionate and exaggarated fear of physical movement that makes one feel helpless (29). It has been accepted that fear or pain leads one to restrict his/her own movements.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that this decrease was disproportionate to the females' lower body mass. Similarly, Reneman et al (2007) found that males out performed females during a high-intensity lifting task. The female subjects demonstrated significantly lower maximal weight that was lifted five times within 90 seconds.…”
Section: Introductionmentioning
confidence: 88%